ASAS-ASAS HUKUM DALAM SISTEM HUKUM - I Dewa Gede Atmadja (Kertha Wicaksana, 2018)
Tulisan ringkas ini focus pada analisis pengertian asas-asas hukum, perbedaan asas hukum dengan norma/kaidah hukum, kedudukan asas hukum, fungsi dan jenis asas-asas hukum dalam sistem hukum. Bahasnnya merupakan rangkuman dari beberapa literatur yang penulis simak pada perpustakaan pribadi. Hasil yang di harapkan dapat membantu para mahasiswa hukum untuk mengenal dan memahami pentingnya asas-asas hukum berkaitan dengan arahan agar aturan hukum niscaya dalam perilaku subyek-subyek hukum. This paper focuses on the analysis of the understanding of legal principles, differences in legal principles with legal norms, legal status, functions and types of legal principles in the legal system. The bahasnnya is a summary of some literature that authors refer to the private library. The expected results can help law students to recognize and understand the importance of legal principles with regard to the directive that the rule of law is inevitable in the behavior of legal subjects.